Repeated Insurance Contracts with Adverse Selection and Limited Commitment - Hosios, Arthur J.; Peters, Michael (Quarterly Journal of Economics, 1989)
In this paper we describe the sequential equilibria of a two-period monopoly with asymmetric information and limited commitment in the market for accident insurance. The role of learning is analyzed; and the possible sequential pooling, semiseparating, and separating equilibria are described (where the probability that a buyer will make a revealing first-period contract choice is equal to zero, is positive, and is equal to one, respectively). In the absence of discounting, we show that only pooling and semiseparating equilibria exist; provide a limited characterization of when these equilibria occur; and show that accident-contingent insurance and accident underreporting occur with positive probability along the equilibrium path of the game.